Desain dan Uji Coba Video Pembelajaran dengan Bantuan Software Wondershare Filmora pada Materi Asam Basa - Rizqi; Arif (Jurnal Riset Pendidikan Kimia (JRPK), 2020)
This research was instigated by the lack of student interest in reading books, so it was needed a media such a tutorial video that could help students understand the lesson. This research aimed at designing a valid tutorial video with Wondershare Filmora software on Acid Base lesson based on validation by the experts of material and media, and the practicality test by teachers and students. It was Research and Development (R&D) with Borg and Gall development model. The steps in this research were 1) researching and collecting information, 2) planning, 3) developing the initial form of the product, and 4) preliminary field testing, 5) revising the product. Preliminary field testing was conducted at the tenth-grade students of Natural Science Ikhwan of Islamic Integrated Senior High School of Al-Fityah Pekanbaru. The validation result by the experts of media and material was 91.25% and it was on very valid criterion. The result of teacher practicality test was 95.13%, and it was on very practical category. The result of student practicality test was 82.7%, and it was on very practical category. Keywords Tutorial Video, Wondershare Filmora, Acid Base<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">